Peran Pengurus Pondok Pesantren Al-Amien Tegal Dalam Membentuk Karakter Mandiri Anak Usia Dini - Haya, Aqila Fadia; Afifah, Muru’atul (Faidatuna, 2024)
The background problem of this research is the importance of forming independent characters in early childhood so they don't depend on others. Considering that now parents are busy working and caring for their children is handed over to the family or household assistants who usually pamper children and accustom children to playing gadgets for the important reason that children are not naughty at home so that a lot happens in their surroundings, small children are used to playing gadgets, it is no longer a taboo sight so that the next generation nowadays many are addicted to games and others. So Islamic boarding schools are a suitable place for the formation of independent character in early childhood.The purpose of this study was to describe the role of the management of the Al-Amien Tegal Islamic boarding school in forming independent character in early childhood as well as the supporting and inhibiting factors for the formation of independent character in early childhood at the Al-Amien Tegal Islamic boarding school.Based on the results of the study it can be seen that the role of the management of the Al-Amien Tegal Islamic boarding school in forming the independent character of early childhood is (1) the supervisisors acts as a second parent (2) as a mentor (3) as a supervisor and (4) as a role model. The supporting factors in the formation of the independent character of early childhood are collaboration between supervisiors and support from parents of early childhood students. While the inhibiting factor is the innate attitude of early age students and facilities and infrastructure.